Oliver Twist ; A tale of two cities ; Great expectations ; A Christmas carol - Dickens, Charles, 1812-1870. (New York : Barnes & Noble, 1992)
Oliver Twist, published in 1838 and set in London's Victorian underworld, is a novel of social protest, a morality tale, and a detective story. A Tale of Two Cities, published in 1859, is Dicken'sss great novel of the French Revolution. Great Expectations, published in 1861, is the story of Pip and the mysterious fortune which falls into his lap. A Christmas Carol is his most beloved story, as much as part of Christmas as mistletoe and carolers.
Keywords: Great Britain -- Social life and customs -- 19th century -- Fiction; France -- History -- Revolution, 1789-1799 -- Fiction; Historical fiction; War stories